Supply Chain Optimization by Mixed Integer Program for Manufacturer and Retailer System of Poultry firm in Bangladesh - Islam, Mohammad Khairul; Uddin, Mohammed Forhad; Alam, Md M (GANIT: Journal of Bangladesh Mathematical Society, 2016)
In this study, we formulate mixed integer program for manufacturer and retailer system of poultry firm in Bangladesh that is one of the most promising sectors to increase Gross Domestic Product (GDP) growth rate plus equitable distribution through arranging food security as well as ensuring self-employment, creating purchasing power and reducing poverty at a large scale. From the survey, it has observed that the selling price of eggs and chicken fluctuate depending on the natural calamities. We have made a question survey on some poultry firm in the district of Mymensingh and Gazipur. This paper maximized the profit and minimizes the cost. The formulated mixed integer program has solved by branch and bound algorithm using A Mathematical Programming Language (AMPL). It has observed that the profit and selling price have very good relationship with production cost and raw materials cost but no significant relation with fixed cost. GANIT J. Bangladesh Math. Soc.Vol. 34 (2014) 75-87